(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate initially first four cases of d-transposition of the great arteries (d-TGA) were diagnosed and treated at Nghe An Obstetrics and Pediatrics Hospital Methods: To present four cases were first diagnosed and operated successfully with ASO. The data was taken from electronic medical records on EHC software of Nghe An Obstetrics and Pediatrics Hospital. The information includes epidemiology, clinical symptoms, and subclinical symptoms before, during and after surgery. Results: Four patients were referred to Nghe An Obstetrics and Pediatrics Hospital at 14 days, 2 month, 26 days, 1 day of age, no prenatal diagnosis, were diagnosed d-TGA after admission. Four patients underwent ASO successfully. Conclusions: There are still many difficulties to diagnose the d-TGA in prenatal and grassroots health care level. Nghe An Obstetrics and Pediatrics Hospital is a center that has ability to diagnose and perform ASO.